ICT and actual working time in Germany - Grunau, Philipp; Wolter, Stefanie; Bellmann, Lutz; Müller, Dana (management revue, 2017)
This study investigates the impact of information and communication technology (ICT) on actual weekly working hours using the second wave of the German Linked Personnel Panel, a unique employer-employee dataset. ICT usage is widespread among employees in the private sector. Half of the establishments equip all managerial employees with mobile devices. We confirm the findings of previous studies that show a positive correlation between ICT usage and working times. Employees work approximately 30 minutes longer per week if they use modern digital technologies for work. Furthermore, our multivariate analyses reveal that this correlation is especially strong for managers and in establishments that equip all of their employees in leading positions with mobile devices